An Examination of Philadelphia Murder: A Quest to Understand the 2004-2006 Surge in Violent Crime - Lynch, Joseph J (2007)
This paper examines the 2004-2006 surge in violent crime, specifically murder in Philadelphia, Pennsylvania. Interviews were conducted with local prominent criminal justice professionals. Interviewees were asked what they believe is wrong with the local criminal justice system, and how the system can be enhanced. Crime predictors were identified and suggestions for mitigating them were offered. The findings suggest that reduced funding, lack of collaboration amongst component agencies rank as leading causes for ineffectiveness. One person stated that due to the war in Iraq and Afghanistan, funding streams for juvenile justice programs have been reduced, resulting in fewer programs designed to provide these youth with needed resources to steer them away from crime. It was suggested that restructuring these agencies will improve their operational goals, and create better accountability and improved relationships with the community. It is also recommended that the agencies working within the criminal justice system pool their resources and collaborate regularly to enhance their effectiveness